THE REALITY OF MARKETING SPORTS FACILITIES IN SOME SPORTS CLUBS IN THE GOVERNORATES OF SOUTHERN IRAQ - Dr. Bahaa Hayder Flayyih; Anwar Hayder Flayyih; Dr. Khalid Aswad Layikh (Proximus Journal Publishing, 2025)
Without money, sports facilities and stadiums cannot be built, nor can players, training and technical staff, and other elements that contribute to building and developing sports be attracted. One of the methods followed by sports clubs is sports marketing activity, which played a major role in providing a very high budget for some international sports clubs. In fact, many Arab countries have started sports marketing activities in their sports clubs, which have clearly shown positive results. If sports clubs invest in sports marketing correctly, according to scientific foundations, and according to a well-studied strategy, it is possible to solve many of the financial problems of Iraqi sports clubs, which are the biggest obstacle to the process of building and developing sports in those clubs, which has been reflected in the level of sports in the country. There is an urgent and necessary need to expand and diversify the revenue channels of sports clubs by establishing marketing work foundations for sports clubs based on the results of research in this field to expand and diversify the base of sports games and then develop them. The most important objectives of the research are to prepare a scale for marketing sports facilities in some sports clubs in the southern governorates, as well as to identify the reality of marketing sports facilities in some sports clubs in the southern governorates. The research sample was identified, and the scale was built and applied on them, and the research data was collected to show us the results, which are: there is a weakness in the process of contracting with companies specializing in sports clothing and equipment, and not benefiting from the halls and lounges in sports clubs and renting them for parties and events.
Keywords: Sports marketing; Sports clubs; Management and organization